Problematika Hukum Pengembalian Aset Tindak Pidana Korupsi Pelaku dan Ahli Warisnya - Arifin, Firdaus (Universitas Muhammadiyah Sumatera Barat, 2019)
Barriers to returning assets can be explained theoretically and practically. Theoretically, there has been a misunderstanding in the understanding of lawmakers and several criminal law experts and financial legal experts in resolving the problem of criminal assets. The first mistake, namely the a priori attitude that criminal law which is oriented to the philosophy of retributive justice is seen as the only legal tool that is considered appropriate for the purpose of restoring state financial losses. While this goal can only be achieved by changing the new paradigm of corrective-rehabilitative and restorative justice. The second mistake, so far the legal approach in the legal process of returning assets of a criminal offense is always used a normative legal approach based on legal positivism.